2018
DOI: 10.1038/s41467-018-05602-w
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the essential peptidoglycan amidotransferase MurT/GatD complex from Streptococcus pneumoniae

Abstract: The universality of peptidoglycan in bacteria underlies the broad spectrum of many successful antibiotics. However, in our times of widespread resistance, the diversity of peptidoglycan modifications offers a variety of new antibacterials targets. In some Gram-positive species such as Streptococcus pneumoniae, Staphylococcus aureus, or Mycobacterium tuberculosis, the second residue of the peptidoglycan precursor, D-glutamate, is amidated into iso-D-glutamine by the essential amidotransferase MurT/GatD complex.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 65 publications
1
29
0
Order By: Relevance
“…Using two complementary approaches, the in vitro pulldown assay and the in vivo interaction assay, we established that DUF1727 is responsible for the interaction between the two proteins MurT and GatD and for complex formation. This observation was confirmed by recent crystallographic structures, where GatD docks to the C terminus of MurT (20,21). Our results, obtained using distinct approaches, showed that DUF1727 is sufficient for the interaction with GatD and, more importantly, is essential for complex activity.…”
Section: Discussionsupporting
confidence: 88%
“…Using two complementary approaches, the in vitro pulldown assay and the in vivo interaction assay, we established that DUF1727 is responsible for the interaction between the two proteins MurT and GatD and for complex formation. This observation was confirmed by recent crystallographic structures, where GatD docks to the C terminus of MurT (20,21). Our results, obtained using distinct approaches, showed that DUF1727 is sufficient for the interaction with GatD and, more importantly, is essential for complex activity.…”
Section: Discussionsupporting
confidence: 88%
“…In another example, the transcriptional regulator, whiA , which is involved in sporulation in Streptomyces ( Bush et al, 2013 ), appears to play a key role in the mycobacterial cell cycle, clustering with other components of cell division ( Figure 7—figure supplement 1C ). Furthermore, MSMEG_6276 – a putative mur ligase – clusters closely with the peptidoglycan synthesis protein, mviN ( Gee et al, 2012 ), and exhibits strong homology to murT/gatD from S. pneumoniae ( Morlot et al, 2018 ; Figure 7—figure supplement 1D ). In combination, these additional examples support the utility of image-based profiling for informing or validating hypothetical or predicted gene function – particularly those involved in cell-wall metabolism or DNA metabolism and cell-cycle regulation.…”
Section: Resultsmentioning
confidence: 99%
“…In those Gram‐positive species where D ‐ iso Gln is found at Position 2, D ‐Glu is enzymatically deamidated to D ‐ iso Gln by an enzyme complex of MurT/GatD . The structure of the MurT/GatD complex has been solved recently, revealing the mechanism of PG amidation by MurT, and also the mechanism through which GatD produces and channels the ammonia required for PG amidation to the MurT active site …”
Section: Pg Synthesismentioning
confidence: 99%